Pengaruh Kecerdasan Logis Matematis Dan Kemampuan Berpikir Kritis Terhadap Prestasi Belajar Matematika - Manzilah, Siti (Jurnal Gemaedu, 2018)
The purpose of this study was to determine the effect of mathematical logical intelligence and students' critical thinking skills on mathematics learning achievement. The method used is a survey. Data collection techniques were carried out by taking UTS values ​​for mathematics learning achievement, spreading test questions for mathematical logical intelligence, and test questions for critical thinking skills. The population is class VII MTs Tanwirul Qulub, the sample is 38 students, with the sampling technique used is purposive sampling technique. Requirements test data analysis using normality test with chi squared with the results of all data are normally distributed and linearity test with the results of all linear pattern data. The results of the study obtained F_count > T table or 11.35> 3.27 at the 0.05 significance level, which means that there is the influence of mathematical logical intelligence and the ability to think critically together on mathematics learning achievement. Conclusions: (1) There is the influence of mathematical logical intelligence and critical thinking skills on mathematics learning achievement, (2) There is the influence of mathematical logical intelligence on mathematics learning achievement, and (3) There is the influence of critical thinking skills on mathematics learning achievement